OPTIMALISASI PENGHIMPUNAN ZAKAT DIGITAL DI MASA PANDEMI - Annisa Zetira; Nur Fatwa (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Since the world health organization (WHO) declared Corona Virus Diseases a pandemic, Indonesia's economic growth has weakened. However, zakat collection funds have increased by 30%. This is due to a shift in lifestyle from offline to online to support policies to prevent the spread of the Corona virus. As long as the social restriction policy is enforced, zakat payments cannot be made directly, so zakat management organizations take advantage of this opportunity by innovating in the field of digital technology to strengthen and optimize zakat collection. Even though there is an increase in the number of zakat collections, based on data from Baznas, the acquisition of zakat funds is still very far from the potential zakat figure, so digital zakat management is needed to reach a wider area of socialization, increase the number of muzakki, and increase the number of zakat collections. So that digital zakat collection can run effectively and efficiently, all zakat management organizations (OPZ) that are not yet running optimally need to carry out zakat management by referring to James Stoner's theory that has been carried out by Baznas and other zakat amil institutions. Starting from planning (planning), organizing (organizing), implementation or direction (actuating), and reporting or monitoring (controlling) by utilizing human resources and other resources. This research is a qualitative research and uses a literature review method. The data used is secondary data, which consists of books, journals, reports, zakat outlook, and other literature related to this research. From the secondary data, it was found that Baznas has carried out zakat management effectively, but there are still OPZs that have not done it effectively. One of them is Baznas at the district or city level which experienced a decrease in the number of OPZ in 2019 because it did not have a permit as an official zakat manager.